2018
DOI: 10.1111/cas.13745
|View full text |Cite
|
Sign up to set email alerts
|

HOTAIR, a long noncoding RNA, is a marker of abnormal cell cycle regulation in lung cancer

Abstract: Dysregulation of the cell cycle is a key indicator of tumors, including lung cancer. Recently, the study of cell cycle inhibitors has made great progress in relation to lung cancer. However, the question of what kinds of patients can use cell cycle inhibitors has plagued us. Therefore, seeking an accurate and convenient marker for the abnormal cell cycle in lung cancer is very important. In the present research, we showed that lncRNA HOTAIR is an optimal indicator of cell cycle dysregulation in lung cancer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…We also found that DEGs were signi cantly enriched in angiogenesis, which is a core hallmark of advanced cancers, especially in LUAD [18][19][20]. Besides, other signi cant GO terms, such as regulation of cell cycle and regulation of small GTPase mediated signal transduction were also related to cancer progression and chemoresistance reported in many studies [21,22]. As shown in Fig.…”
Section: Functional Enrichment Of Dmgssupporting
confidence: 59%
“…We also found that DEGs were signi cantly enriched in angiogenesis, which is a core hallmark of advanced cancers, especially in LUAD [18][19][20]. Besides, other signi cant GO terms, such as regulation of cell cycle and regulation of small GTPase mediated signal transduction were also related to cancer progression and chemoresistance reported in many studies [21,22]. As shown in Fig.…”
Section: Functional Enrichment Of Dmgssupporting
confidence: 59%
“…Another study also showed that MALAT1 interacted with a nuclear protein hnRNP C that is functionally involved in G2/M phase [ 106 ]. Other lncRNAs including HOTAIR [ 107 , 108 ], HOXA11-AS [ 40 ], lncRNA-HEIH [ 109 ], MEG3 [ 110 ], ncRNA CCND1 [ 111 ], and PANDA [ 39 , 112 ] are reported with their significant roles in regulating the expression of cell cycle regulators and respective cell cycle stages (Table 3 ).…”
Section: Functional Targets For Probing Biological Effects Of Lncrnasmentioning
confidence: 99%
“…HOTAIR could be regarded as a potential indicator of cell cycle dysregulation in lung cancer. 10 MEG3 was down-regulated in ovarian cancer cells and elicited tumor inhibitor role in this disease. 11 Besides, lncRNAs have also been reported to affect tumor growth, metastasis, and drug resistance by controlling target gene expression and pathway activation.…”
Section: Introductionmentioning
confidence: 95%